Higher Cerebral Blood Flow Predicts Early Hematoma Expansion in Patients With Intracerebral Hemorrhage: A Clinical Study - Wang, Weijing; Jin, Weitao; Feng, Hao; Wu, Guoliang; Wang, Wenjuan; Jia, Jiaokun; Ji, Ruijun; Wang, Anxin; Zhao, Xingquan (Frontiers in Neurology, 2021)
The early hematoma expansion of intracerebral hemorrhage (ICH) indicates a poor prognosis. This paper studies the relationship between cerebral blood flow (CBF) around the hematoma and hematoma expansion (HE) in the acute stage of intracerebral hemorrhage. A total of 50 patients with supratentorial cerebral hemorrhage were enrolled in this study. They underwent baseline whole-brain CTP within 6 h after intracerebral hemorrhage, and non-contrast CT within 24 h. Absolute hematoma growth and relative hematoma growth were calculated, respectively. A relative growth of Hematoma volume >33% was considered to be hematoma expansion. The Ipsilateral peri-edema CBF and Ipsilateral edema CBF were calculated by CTP maps in patients with and without hematoma expansion, respectively. In this study the incidence of hematoma expansion in the early stage of supratentorial cerebral hemorrhage was 32%; The CBF of the hematoma expansion group was higher than that of the patients without hematoma expansion (23.5 ± 12.5 vs. 15.1 ± 7.4, P = 0.004). After adjusting for age, gender, Symptom onset to NCCT and Baseline hematoma volume, ipsilateral peri-edema CBF was still an independent risk factor for early HE (or = 1.095, 95% CI = 1.01–1.19, P = 0.024). Here, we concluded that higher cerebral blood flow predicts early hematoma expansion in patients with intracerebral hemorrhage.